P75. Transcranial direct current stimulation (tDCS) of the midline cerebellum does not facilitate learning of a complex whole body dynamic balance task. Issue 8 (August 2015) - Thier, W.; Ludolph, N.; Ilg, W.; Timmann, D.
<x xml:space="preserve">Abstract</x> The purpose of this study was to investigate if cerebellar tDCS facilitates learning of a complex whole body motor skill. 36 young and healthy subjects participated in 2 days of balance training on a Lafayette Instrument 16030 stability platform®. Training consisted of 15 trials, 30 s each, on day 1 and 7 trials on day 2. On day 1, twelve subjects received anodal, 12 subjects cathodal and 12 subjects sham tDCS over the midline cerebellum (electrode size 7 × 5 cm2, center of the upper end 2.5 cm above the inion; current intensity 2.8 mA; Neuroconn® DC Stimulator). As measures of balance performance mean platform angle deviation and mean balance time were assessed in each trial. Balance time was defined as the time, in which subjects were able to hold the platform between −5° and 5° relative to earth horizontal (0°). All groups exhibited significant improvement of balance over the course of the two training days which, however, was not significantly modulated by stimulation (trial effect: p < 0.001; block × stimulation interaction: p > 0.64; ANOVA with repeated measures). Yet, a main effect of stimulation with worse performance during cathodal compared to anodal stimulation was found (p < 0.05). Surprisingly, this effect was observed only in males (stimulation effect: p < 0.02; trial × stimulation: p > 0.42) and not in females. On average, males were taller than females and performance measures correlated negatively with body height. In conclusion, tDCS of the midline cerebellum did not facilitate learning of a complex whole body dynamic balance task in young and healthy subjects. This negative finding disappoints expectations somewhat, yet does not exclude the possibility, that tDCS might facilitate balance training of cerebellar patients. However, baseline performance was modulated by tDCS in males in a polarity-dependent manner. The gender difference might be a consequence of larger body size, arguably rendering taller subjects more sensitive to a modulatory influence of tDCS in the examined task. Acknowledgement Supported by the <funding-source id="gp005" xlink:type="simple" xlink:role="http://www.elsevier.com/xml/linking-roles/grant-sponsor" xlink:href="" xmlns:xlink="http://www.w3.org/1999/xlink">Bernd-Fink Foundation</funding-source>.